Morphological features of bovine placenta in case of viral, bacterial and protozoal infections - O. V. Sokolova; L. I. Drozdova; I. A. Shkuratova (Ветеринария сегодня)
The problem of the intrauterine  infection of fetus is one of the most critical ones in veterinary obstetrics and in perinatology due to the high level of infection in pregnant  cows, the risk of developmental disorder of fetus and the birth of sick calves. Complications of pregnancy occur in case of viral, bacterial and protozoal infections, when the pathogen  enters the uterus in an ascending or descending way with further transplacental  infection of the fetus. Morphological studies of placenta  of Black Pied cattle infected with bovine viral diarrhea, chlamydia and neosporosis were carried out. The presence of the pathogen was confirmed by serological and molecular genetic methods. The material used for histological studies was the fetal part of placenta. After sampling, the material was fixed in a 10% neutral formalin solution, then xylene-free method  for histological preparation  was used. Afterwards, samples were embedded in paraffin. In order to study morphological structures, samples were sectioned at 5–6 µm, and stained with hematoxylin and eosin. Histological sections were analyzed using a Leica DM 1000 light microscope at a magnification of 100×,  200×,  400×,  630×.  On the basis of the conducted studies, it was established that bovine viral diarrhea-associated morphofunctional changes in the “mother – placenta – fetus” system are characterized by involutive-dystrophic changes with microcirculation disorders and the development of an immunity-associated inflammatory process. Chlamydia abortus intrauterine  infection in the “mother – placenta – fetus” system in cows causes a complex of destructive morphological and functional changes of an infectious and toxic nature with a pronounced inflammatory reaction, involvement of blood vessels in the pathological process, and endothelial dysfunction development,  alongside with tissue necrosis in case of a chronic process. The presence of cellular structures in the placenta and the inner part of the umbilical cord is a pathognomonic sign of chlamydia. The role of transplacental transmission of Neospora caninum in cattle was confirmed, the Neospora parasites subjected to basophilic staining were detected not only in the tissues of the placenta, but also in histological sections of the fetus heart and liver. The main characteristic diagnostic sign is the presence of basophilic stained Neospora parasites  in the organs of the mother  and fetus, placenta, and intervillous space. As part of the study morphological features of placenta, one of the most unique histohematic barriers and the basic element of the intrauterine infectious process, were determined.